2023
DOI: 10.3390/ani13132184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Storage on Hatchability and Incubation Length of Game Farmed Quail Eggs

Pedro González-Redondo,
Pascual Robustillo,
Francisco P. Caravaca

Abstract: The long-term storage of eggs before incubation is a common practice in some alternative poultry systems but needs to be performed under conditions that preserve egg viability. The effects of the long-term storage of game farmed quail (Coturnix coturnix) eggs on weight loss during the storage and incubation periods, chick weight at hatch, hatchability, and incubation length were investigated. The eggs were arranged in six treatments submitted to 0-, 7-, 14-, 21-, 28-, and 35-day storage periods at 15.8 °C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Also, hatchability increased until a certain point and then decreased because the pre-incubation intervals were stored for longer periods (up to 7 d), according to Uddin et al (1994) . Furthermore, González-Redondo et al (2023) found that quail eggs' longer storage times led to a noticeably lower hatchability percentage. Long-term egg storage decreased the hatchability of viable and set eggs and increased the percentage of embryonic deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, hatchability increased until a certain point and then decreased because the pre-incubation intervals were stored for longer periods (up to 7 d), according to Uddin et al (1994) . Furthermore, González-Redondo et al (2023) found that quail eggs' longer storage times led to a noticeably lower hatchability percentage. Long-term egg storage decreased the hatchability of viable and set eggs and increased the percentage of embryonic deaths.…”
Section: Discussionmentioning
confidence: 99%
“…It is advised not to keep broiler and laying hen breeders' eggs for more than 7 d ( Archer and Cartwright, 2012 ; Özlü, 2021 ). Research indicates that eggs lose a substantial amount of viability after 2 wk of storage ( González-Redondo et al, 2023 ). Conversely, some bird species' eggs may withstand longer storage periods before incubation without deleterious impacts on their hatchability.…”
Section: Introductionmentioning
confidence: 99%